Tunable magnetic and magnetotransport properties in locally epitaxial La0.67Sr0.33MnO3 thin films on polycrystalline SrTiO3, by control of grain size. (9th June 2022) - Dallocchio, Marie; Boileau, Alexis; Mercey, Bernard; David, Adrian; Lüders, Ulrike; Froissart, Sandrine; Larose, Xavier; Bérini, Bruno; Dumont, Yves; Pautrat, Alain; Prellier, Wilfrid; Fouchet, Arnaud
Abstract: La0.67 Sr0.33 MnO3 (LSMO) thin films have been grown by pulsed laser deposition on SrTiO3 using combinatorial substrate epitaxy (CSE) approach, i.e. polycrystalline substrates with micrometer-size grains. The crystallographic domains size of those polycrystalline substrates can be controlled between 2 and 45 µ m depending on the annealing temperature during synthesis. Each grain of the substrate acts as a single crystalline growth template promoting local epitaxy with a reproduction of the substrate grain structure in the thin film. Therefore, a fine-tuning of the substrate grain metrics and high crystalline quality of locally epitaxial LSMO film, allows to combine the advantages of polycrystalline, i.e. the presence of low field magnetoresistance (LFMR) and the possibility to use very thin films, with a pronounced magnetic shape anisotropy. For this, the magnetic and transport properties of the films are showing a strong influence with varying grain metrics of the substrate. High Curie temperatures, important values of the LFMR and anisotropy for optimized substrate grain metrics with the relative orientation of the magnetic field to the film plane underline the high quality of the films and the advantage of the CSE approach. The obtained LSMO thin films may have an interest for high-resolution low field magnetic sensors application.